2001
DOI: 10.1055/s-2001-19926
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Approach to Traumatic Intracerebral Hematomas

Abstract: Trauma is one of the leading causes of death in Brazil. We report on 28 cases of traumatic intracerebral hematomas operated on via a minimally invasive approach. A simplified method of localization and right placement of the burr hole is described in details, as well as the technique used in all cases. Every patient was submitted to pre- and postoperative CT scan (computerized tomography) and had the volume of the hematoma measured before the surgical procedure to compare the efficacy of the treatment. No pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
0
1
Order By: Relevance
“…For surgically treated traumatic ICH patients, our favorable outcome of 97.1% was significantly higher than the 62% in the United Kingdom and the 63% reported in the first randomized trial (STITCH) for traumatic ICH patients in 31 centers from 13 countries [ 29 , 30 ]. Our mortality rate of 2.9% was prominently lower than the 10% in Brazil or the 15% reported in 31 centers from 13 countries [ 30 , 31 ]. Therefore, we concluded that the surgical treatment of traumatic ICH patients in the study hospital was acceptable.…”
Section: Discussioncontrasting
confidence: 75%
“…For surgically treated traumatic ICH patients, our favorable outcome of 97.1% was significantly higher than the 62% in the United Kingdom and the 63% reported in the first randomized trial (STITCH) for traumatic ICH patients in 31 centers from 13 countries [ 29 , 30 ]. Our mortality rate of 2.9% was prominently lower than the 10% in Brazil or the 15% reported in 31 centers from 13 countries [ 30 , 31 ]. Therefore, we concluded that the surgical treatment of traumatic ICH patients in the study hospital was acceptable.…”
Section: Discussioncontrasting
confidence: 75%